Mutu Kimia Dan Organoleptik Permen Jelly Rumput Laut Gelatin Sapi - Maya Novitasari; Mappiratu Mappiratu; Dwi Sulistiawati (Universitas Tadulako, 2016)
Jelly has a supple and elastic texture. Jelly is one kind of product that attracted many people because the texture is different compared to other sweets. One of the factors that affect the quality of jelly is the gel-forming material. This study aims to determine the ratio of seaweed to cow’s gelatin that can produce jelly which has a good chemical and organoleptic quality. The experimental design used in this research is completely randomized design (CRD) with a combination of patterns is a difference ratio of seaweed and cow’s gelatin repeated 3 times so that there are 18 units of the experiment. Chemical parameters were observed consisting of ash and total sugar. Organoleptic parameters were observed consisting of taste and firmness. Jelly that produced in this research had 0.43 to 0.68% ash content and total sugar content 33, -53.67% and it has the organoleptic quality preferred by the panelists. Jelly that produced in this research is still meet the quality standard ISO 3574.2-2008.